Married men and early retirement under AFP scheme - Ole J. Røgeberg (University of Oslo, Department of Economics, 2000)
The following thesis concerns itself with the labour supply of elderly married men eligible for early retirement under the AFP (AvtaleFestet Pensjonsordning) scheme. Retirement behaviour is a theme of increasing importance as demographic changes lead to higher proportions of elderly individuals in the population, and as pay-as-yougo public pension systems threaten to become an increasingly heavy fiscal weight for the governments of many social democracies. The subject is one where Economics should be able to contribute, with its studies of incentives and behaviour, and it is one in which economists have shown a lot of interest. All the same, there are parts of this subject less examined than others, often because researchers have difficulties procuring good empirical data for analysis. One such part is the interplay between spouses in a household, a subject which may prove to be important as the cohorts with higher female labour force participation rates age. Using extensive register data, the project “Pension schemes, work activity and retirement behaviour” conducted at the Frisch Centre, hopes to be able to increase our understanding of the dynamics here at play. This paper serves as a documentation of the data underlying one of the papers published as a part of this project.
Keywords: 330; Flexible Altersgrenze; Ältere Arbeitskräfte; Männer; Arbeitsangebot; Arbeitsmarktpolitik; Norwegen